Navigating adversity: the relationship between academic entitlement and resilience in male undergraduates - Badawy, Mahmoud Elsaid; Soliman, Tawfik; Nemt-allah, Mohamed Ali (Institute of Advanced Engineering and Science, 2025)
In today’s academic landscape, there is growing concern about the rise of academic entitlement among students and its potential impact on their psychological resilience. This study aimed to examine the relationship between academic entitlement and psychological resilience among university students, and to determine if academic entitlement subscales can predict resilience. The participants were 746 male undergraduate students from the Faculty of Education at Al-Azhar University, aged 19-25 years (M=21.41, SD=.952). Students completed the academic entitlement scale (AES) and the Connor-Davidson Resilience Scale (CD-RISC). The results revealed a significant negative correlation between overall academic entitlement and psychological resilience (r=-.801, p<.01), supporting the first hypothesis. Multiple regression analysis showed that both academic narcissism (β=-.237, p<.001) and academic outcome (β=.132, p<.001) subscales were significant predictors of psychological resilience, confirming the second hypothesis. These findings suggest that addressing entitled attitudes and fostering resilience should be key priorities for higher education institutions. Implications include developing targeted interventions to reduce academic entitlement and enhance resilience among students, potentially improving their academic performance and psychological well-being. Future research should explore additional factors influencing this relationship and evaluate the effectiveness of interventions across diverse student populations.